2011
DOI: 10.1080/17461391.2011.566359
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of hot pack on symptoms of eccentric exercise‐induced muscle damage of the wrist extensors

Abstract: This study investigated whether hot pack treatment could provide prophylactic effects on muscle damage induced by eccentric exercise of the wrist extensors. Twenty-eight healthy men (age 2191 years, weight 65916 kg, height 17196 cm) were randomly placed into hot pack (n 0 14) and control (n 0 14) groups. All participants performed an exercise consisting of 300 maximal eccentric contractions of the wrist extensors of the non-dominant arm using an isokinetic dynamometer. A hot pack was applied for 20 min to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Khamwong et al found beneficial effects when participants applied hot packs [23] or entered a sauna [24] before eccentric exercise. Specifically, both hot packs and sauna reduced the loss in range of motion of the wrist resulting from eccentric exercise.…”
Section: Human Studiesmentioning
confidence: 99%
“…Khamwong et al found beneficial effects when participants applied hot packs [23] or entered a sauna [24] before eccentric exercise. Specifically, both hot packs and sauna reduced the loss in range of motion of the wrist resulting from eccentric exercise.…”
Section: Human Studiesmentioning
confidence: 99%
“…6 DOMS is usually cited by coaches and athletes as being detrimental to recovery and performance, the rapid reversion of DOMS in athletes is essential for both function restoration and regain of sports performance. 6,7 Therefore, several modalities of recovery have been used to hasten the recovery period from DOMS which include warm-up and cool-down, 8 soft tissue massage, 3 stretching exercise, 9 electrotherapy, 10 thermotherapy 11 and cryotherapy. 7,12 However, the efficacy of such interventions on exercise induced muscle damage remains equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Massage can reduce the tension on the muscle tendon unit that affects the visco-eleastic component of the tissue leading to an increase in competence of the muscle and improvement of muscular flexibility reducing muscle stiffness and also increasing blood flow [14]. Researchers have demonstrated that massage has preventive effects ,decrease muscle soreness and other symptoms [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%